Microporous methacrylated glycol chitosan-montmorillonite nanocomposite hydrogel for bone tissue engineering - Zhong-Kai Cui (Nature Portfolio, 2019)
Injectable hydrogels could be used to repair bone defects. Here the authors incorporate nanoclay particles into chitosan creating an interconnected microporous hydrogel and show that this hydrogel can support MSC proliferation and differentiation in vitro, and support the recruitment of native cells and bone regeneration in a mouse calvarial defect model.